Seismic Azimuthal Anisotropy Beneath the Alaska Subduction Zone - Chuanming Liu; Anne F. Sheehan; Michael H. Ritzwoller (Geophysical Research Letters, 2024)
AbstractWe estimate depth‐dependent azimuthal anisotropy and shear wave velocity structure beneath the Alaska subduction zone by the inversion of a new Rayleigh wave dispersion dataset from 8 to 85 s period. We present a layered azimuthal anisotropy model from the forearc region offshore to the subduction zone onshore. In the forearc crust, we find a trench‐parallel pattern in the Semidi and Kodiak segments, while a trench‐oblique pattern is observed in the Shumagins segment. These fast directions agree well with the orientations of local faults. Within the subducted slab, a dichotomous pattern of anisotropy fast axes is observed along the trench, which is consistent with the orientation of fossil anisotropy generated at the mid‐ocean ridges of the Pacific‐Vancouver and Kula‐Pacific plates that is preserved during subduction. Beneath the subducted slab, a trench‐parallel pattern is observed near the trench, which may indicate the direction of mantle flow.